2021
DOI: 10.1542/peds.2020-030692
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Emergency Department Length of Stay for US Pediatric Mental Health Visits (2005–2015)

Abstract: BACKGROUND AND OBJECTIVES: Children seeking care in the emergency department (ED) for mental health conditions are at risk for prolonged length of stay (LOS). A more contemporary description of trends and visit characteristics associated with prolonged ED LOS at the national level is lacking in the literature. Our objectives were to (1) compare LOS trends for pediatric mental health versus non–mental health ED visits and (2) explore patient-level characteristics associated with prolonged LOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…Nash et al ( 2021 ) recently focused on the issue of prolonged ED stays, analyzing 2005 to 2015 data in 36,125 records from the National Hospital Ambulatory Medical Care Survey. During that 11-year period, the rates of pediatric ED mental health visits greater than six hours in length increased from 16.3% of all visits to 24.6%, while lengths of stay for non-mental health visits remained essentially unchanged.…”
Section: Categories Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nash et al ( 2021 ) recently focused on the issue of prolonged ED stays, analyzing 2005 to 2015 data in 36,125 records from the National Hospital Ambulatory Medical Care Survey. During that 11-year period, the rates of pediatric ED mental health visits greater than six hours in length increased from 16.3% of all visits to 24.6%, while lengths of stay for non-mental health visits remained essentially unchanged.…”
Section: Categories Of Informationmentioning
confidence: 99%
“…The authors found that increased lengths of stay correlated with patient dissatisfaction, ED discharge without being seen by a physician, and increased costs of patient monitoring by ED medical and security staff. Nash et al (2021) recently focused on the issue of prolonged ED stays, analyzing 2005 to 2015 data in 36,125 records from the National Hospital Ambulatory Medical Care Survey. During that 11-year period, the rates of pediatric ED mental health visits greater than six hours in length increased from 16.3% of all visits to 24.6%, while lengths of stay for non-mental health visits remained essentially unchanged.…”
Section: Extended Lengths Of Stay and Boardingmentioning
confidence: 99%
“…This mental health crisis began before the COVID‐19 pandemic 3 but has only worsened in the wake of its resulting social isolation. During the pandemic, suicide hotlines had a 1000% increase in call volumes 4 .…”
Section: Topic Recommendationmentioning
confidence: 99%
“…A patient in the throes of psychosis or suicidality needs a therapeutic milieu, not one that interrupts their daily routine, 2 disconnects them from their existing support networks, and is punctuated by the incessant clangs of bedside monitors and the hubbub of code teams. These environments are not therapeutic 3 for young infants with fevers, let alone for teenagers battling suicidality and eating disorders. In fact, for these reasons, we suspect that many of our patients’ inpatient “behavioral escalations” are in fact triggered by their hospital environment, which may contribute to the 300% increase in the number of pharmacological restraints used during mental health visits in the ED over the past 10 years 9 …”
Section: Topic Recommendationmentioning
confidence: 99%
“…Health inequities-disparities that are unfair, unjust, avoidable, and unnecessary-are ubiquitous among pediatric populations. 1 Health inequities among Black and Hispanic children are well documented in the literature [1][2][3][4][5][6][7][8][9][10][11][12] and are often inappropriately attributed to underlying genetic differences. However, race is a social construct and has no biological basis.…”
mentioning
confidence: 99%